Disentangling the Equavalent Meaning and Diction of Qur’anic Texts: Theory of al-Haml ‘ala al-Ma‘na - Yusuf, Muhammad (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2019)
This paper aims to explain a theoretical concept of al-haml ‘ala al-ma‘na or muru‘at al-ma‘na to evidence a correlation between meanings and texts. It states that text should be inferior to the meaning. Based on our inquiry, verbs should be formed in the feminine (mu’annath) in two situations: first, if verbs consist of ism zahir (visible noun), mu’annath haqiqi (actual feminine), and no texts are bridging the verb. Second, if verbs consist of ism mustatir (invisible noun) with which the subject (fa‘il) is in actual feminine or allegorical feminine (mu’annath majazi). Thus, the masculine or feminine form should be based on their respective meaning. The careless interpretation in constructing meaning may lead to an error understanding, which is contrary to its original meaning. To avoid this, some approaches are needed, such as semantics, ma‘ani, siyaq al-kalam, and asbab al-nuzul.